Perceived quality of privacy protection regulations and online privacy concern. Issue 1 (1st January 2019) - Škrinjarić, Bruno; Budak, Jelena; Rajh, Edo
Abstract: This study examines the impact of regulation as an antecedent of online privacy concern. Previous research found that perceived effectiveness and enforcement of regulatory policies reduce online privacy concern; however, it does not explain what factors influence this relationship. Based on the survey data, the empirical analysis is conducted on a large sample of internet users in Croatia. Our methodology consists of two parts: first, we use confirmatory factor analysis to validate the latent constructs used in the main model; and then we proceed with model estimation using OLS and ordered probit techniques. This study fills the gap in the existing body of knowledge by analysing different perceptions of the existing legislation and government effort to protect online privacy in the context of sociodemographic characteristics of respondents, computer anxiety, individual desire to maintain control of personal information online, as well as intensity and diversity of online activities. Our results indicate that perceived effectiveness of government regulation reduces online privacy concern whereas computer anxiety has a major positive impact on online privacy concern. These findings might be useful for national policy-makers and for business strategies, especially in the context of the GDPR regulation introduced in 2018.